Author response: Diagnostic criteria in amyotrophic lateral sclerosis: A multicenter prospective study. (14th February 2017) - Geevasinga, Nimeshan; Menon, Parvathi; Scherman, Daniel B.; Simon, Neil; Yiannikas, Con; Henderson, Robert D.; Kiernan, Matthew C.; Vucic, Steve
Abstract : We thank Dr. Ali for the review of our article 1 and for the identification of 2 typographical errors. In the Results, the correct number of patients with ALS is 233 (page 686, column 2, line 3), while the number of non-ALS mimic cases is 183 (page 686, column 2, line 5). The correct and detailed number of ALS/non-ALS mimic patients is outlined in table 1. 1